Prostaglandin E2 affects in vitro maturation of bovine oocytes - Dorota Boruszewska; Ilona Kowalczyk-Zieba; Katarzyna Suwik; Joanna Staszkiewicz-Chodor; Joanna Jaworska; Krzysztof Lukaszuk; Izabela Woclawek-Potocka (BMC, 2020)
Abstract The role of prostaglandin E2 (PGE2) in the successful resumption of oocyte meiosis and cumulus expansion has been well-documented. However, there remains very little information available on the influence of PGE2 on other processes that occur during oocyte maturation. In this study, we supplemented a maturation medium with PGE2 and monitored oocyte quality markers, glucose metabolism, mitochondrial status, oxidative stress, and apoptosis in the cumulus-oocyte complexes (COCs), using a well-established in vitro model of embryo production in cattle. We found that this increased availability of PGE2 during maturation led to an increase in the expression of genes associated with oocyte competence and improved the quality of blastocysts produced. Prostaglandin E2 also appeared to stimulate glucose uptake and lactate production in the COCs, both influencing the expression of enzymes involved in glycolysis and the hexosamine biosynthetic pathway. We found that PGE2 reduced intracellular reactive oxygen species levels, and simultaneously increased glutathione concentration and stimulated antioxidant gene expression in the oocyte. These results indicate that PGE2 has an important role in the protection of oocytes against oxidative stress. Mitochondrial membrane potential was also improved in PGE2-treated oocytes, and there was a reduction in the occurrence of apoptosis in the COCs. Promotion of an anti-apoptotic balance in transcription of genes involved in apoptosis was present in both oocytes and the cumulus cells. In summary, PGE2 could represent a novel autocrine/paracrine player in the mechanisms that can facilitate successful oocyte maturation and oocyte survival in the cow.